Principles of Radiological Physics - Graham, Donald T.; Cloke, Paul J. (Edinburgh : Churchill Livingstone, 2003)
This is a comprehensive but easy to follow textbook for radiography students. The physics included reflects current practice in diagnostic imaging, and sections on radiation protection have been updated in line with current legislation.
Previous ed.: 1996.
Includes index.
Formerly CIP.
Keywords: Medical physics; Radiology, Medical